Virtual reality training in laparoscopic colorectal surgery - Rencuzogullari, Ahmet; Gorgun, Emre (Annals of Laparoscopic and Endoscopic Surgery, 2017)
Due to the critical balance between patient safety and long learning curves for new surgical techniques, there has been rising interest in ex vivo surgical training models using simulators.